Manejo pré-abate de bovinos de corte no Pantanal, Brasil - Andrade, E. N. [UNESP] (2009)
This study has the objective of evaluate the influence of fluvial and road transport on the occurrence of bruising in carcass of slaughtered beef cattle. In this study was observed that from 209 evaluated carcass, 185 (88.5%) presented one or more lesions. In total of evaluated carcass occurred 523 lesions that resulted in 96.158 kg removal of bruises (0.519 kg per animal). In this study was possible the determination of age of bruises by color evaluation. We concluded that of way of transport influenced the occurrence of bruises. The most bruises occurred in the last 24 hours of transport. Educational measures will be necessary to reduce the problems of pre-slaughter management.